2011
DOI: 10.1164/rccm.201009-1440oc
|View full text |Cite
|
Sign up to set email alerts
|

Slug Confers Resistance to the Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor

Abstract: Slug contributes to the resistance to gefitinib and may be a potential therapeutic target for treating resistance to EGFR TKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 36 publications
7
128
0
3
Order By: Relevance
“…The results of microarray and real-time RT-PCR showed an increase in cyclin D1 expression, which may explain how YWHAZ promotes cell proliferation and tumorigenesis. Another target gene of b-catenin, Slug, is an important transcription factor that promotes tumor growth, invasion, and drug resistance (8,42,43). On the basis of our current data, we also found enhanced expression of Slug in presence of YWHAZ expression.…”
Section: Discussionsupporting
confidence: 72%
“…The results of microarray and real-time RT-PCR showed an increase in cyclin D1 expression, which may explain how YWHAZ promotes cell proliferation and tumorigenesis. Another target gene of b-catenin, Slug, is an important transcription factor that promotes tumor growth, invasion, and drug resistance (8,42,43). On the basis of our current data, we also found enhanced expression of Slug in presence of YWHAZ expression.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore the identification of new molecular mechanism of EGFR-TKIs and more effective treatments in NSCLC is extremely ultimate goal of cure and long-term control of NSCLC. Currently Chang et al (2011) [3] showed that Slug, the regulator of epithelial-mesenchymal transition (EMT) contributes to the resistance of EGFR-TKIs as gefitnib in NSCLC and [21] showed Notch-1 contributes to EGFR-TKIs acquired resistance in NSCLC, suggesting that Slug and Notch-1 might play a novel role in acquired resistance to gefitinib which could be reversed by inhibiting Slug and Notch-1 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis was that the promotion of EMT by EGFL7 may induce the development of tumor cell resistance to chemotherapy; EMT is regulated by EGFR-mediated AKT phosphorylation induced by EGFL7, which then activates Snail and the subsequent suppression of E-cadherin transcription (27). Numerous studies have previously reported that EMT may have a function in acquired chemoresistance (28)(29)(30)(31)(32). The third hypothesis considered that EGFL7 may have a role in the development of tumor chemoresistance through an increased resistance to cell apoptosis induced by the activation of Snail.…”
Section: No Of Patients --------------------------------------------mentioning
confidence: 99%
“…Luo et al (27) reported that the expression of EGFL7 in gastric cancer cells promotes the epithelial-to-mesenchymal transition (EMT) and tumor metastasis by epidermal growth factor receptor (EGFR)-mediated protein kinase B (AKT) phosphorylation, which subsequently activates Snail and suppresses the transcription of E-cadherin. Numerous studies have demonstrated that increased EMT may lead to chemoresistance in bladder, lung, breast and ovarian cancers (28)(29)(30)(31)(32). In addition, Vega et al (33) reported that Snail inhibits the cell cycle and confers resistance to TGF-β-induced cell death, consistent with Snail activating the Mek/Frk and PI3K/Akt survival pathways.…”
Section: Introductionmentioning
confidence: 95%